1991
DOI: 10.1073/pnas.88.21.9508
|View full text |Cite
|
Sign up to set email alerts
|

Autophosphorylation in vitro of recombinant 42-kilodalton mitogen-activated protein kinase on tyrosine.

Abstract: Mitogen-activated protein kinase (MAP kinase) is a serine/threonine protein kinase that becomes enzymatically activated and phosphorylated on tyrosine and threonine following treatment of quiescent cells with a variety of stimulatory agonists. Phosphorylation on both tyrosine and threonine is necessary to maintain full activity, and these two regulatory phosphorylations occur close to each other, separated by a single glutamate. To study the mechanisms by which MAP kinase becomes phosphorylated and activated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
93
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 139 publications
(98 citation statements)
references
References 26 publications
5
93
0
Order By: Relevance
“…Even prior to the in vitro autophosphorylation, MAPK had some basal MBPphosphorylating activity which can be explained by the presence of the Tyr-phosphorylated form of enzyme in the original preparation of recombinant MAPK, as revealed by blotting with antiphosphotyrosine PY20 (data not shown). Phosphoamino acid analysis of in-vitro autophosphorylated Xenopus MAPK confirmed that Tyr is the major site of autophosphorylation with a minor substoichiometric phosphorylation of Ser, as reported earlier been demonstrated to be intramolecular (Robbins et al, 1993;Wu et al, 1991). In this study, the intramolecular character of Xenopus MAPK autophosphorylation on Tyr was confirmed in three kinds of experiments.…”
Section: Methodssupporting
confidence: 68%
See 4 more Smart Citations
“…Even prior to the in vitro autophosphorylation, MAPK had some basal MBPphosphorylating activity which can be explained by the presence of the Tyr-phosphorylated form of enzyme in the original preparation of recombinant MAPK, as revealed by blotting with antiphosphotyrosine PY20 (data not shown). Phosphoamino acid analysis of in-vitro autophosphorylated Xenopus MAPK confirmed that Tyr is the major site of autophosphorylation with a minor substoichiometric phosphorylation of Ser, as reported earlier been demonstrated to be intramolecular (Robbins et al, 1993;Wu et al, 1991). In this study, the intramolecular character of Xenopus MAPK autophosphorylation on Tyr was confirmed in three kinds of experiments.…”
Section: Methodssupporting
confidence: 68%
“…Thus, the single-site autophosphorylation on Tyr accounts for the observed activation of Xenopus MAPK. Significant (25-45 %) Tyr phosphorylation of mammalian MAPK during the bacterial expression has been reported (Wu et al, 1991). However, our preparation of Xenopus MAPK contained only about 0.5 % of the initially Tyr-phosphorylated enzyme (data not shown), which made it possible to register activation upon autophosphorylation without the separation of phosphorylated and unphosphorylated forms (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations